ON THE EXPERIENCE OF BLENDED LEARNING IN THE BASICS OF PROGRAMMING AT THE FACULTY OF MATHEMATICS AND PROGRAMMING TECHNOLOGIES OF THE FR. SKORYNA GSU - M. S. Dolinsky (Цифровая трансформация)
The article considers the practical experience of mixed teaching first-year students the programming framework on the use of distance learning tool system DL.GSU.BY developed at the GSU. The main factors of increasing the intensity and quality of the learning process are illustrated: the integration of theory and practice, automated personalized learning, automatic knowledge testing, support and encouragement of independent work, automatic permanent visualization of the score sheet.